IONPs combined with cytarabine downregulated IFITM3 expression to inhibit acute myeloid leukemia - Dou, Jun; Mei, Feng; Xu, Hui; Rui, Xue; Bao, Xueyang; Liu, Kena; Zhao, Fengsu (Frontiers in Oncology, 2025)
Background and objectiveAcute myeloid leukemia (AML) is the most prevalent acute leukemia in adults. While conventional therapies can induce remission disease frequently relapses with fatal outcomes. This study aimed to explore the inhibitory effect of iron oxide nanoparticles (IONPs) combined with cytarabine (Ara-C) on AML by modulating the interferon-induced transmembrane protein 3 (IFITM3) expression of in KG-1a cells and AML-bearing mice.MethodsA lentiviral vector targeting IFITM3 (LV-shIFITM3) was used to transduce human AML KG-1a cells, and the biological effects of IFITM3 knockdown were assessed. NOD/SCID mice were engrafted with LV-shIFITM3-KG1a cells and their survival status as well as abnormal cell population were monitored.ResultsCompared to control cells, IFITM3 expression level in the LV-shIFITM3 transduced KG-1a cells exhibited reduced IFITM3 expression, leading to suppressed proliferation, impaired clonogenicity, cell cycle arrest, and increased apoptosis. The combination of IONPs and Ara-C further diminished IFITM3 level, inhibited KG-1a proliferation, and induced apoptosis while elevating reactive oxygen species (ROS) production. In vivo, IONPs plus Ara-C treatment reduced immature granulocytes in peripheral blood and bone marrow, downregulated AML-associated markers (clustered differentiation(CD)33 and CD11b), and ameliorated disease progression in AML-bearing mice compared to controls.ConclusionIFITM3 knockdown in KG-1a cells inhibited proliferation and promoted apoptosis. The combination of IONPs and Ara-C may represent a promising therapeutic strategy for AML by suppressing IFITM3 expression, enhancing ROS levels, and inducing apoptosis. These findings suggest IFITM3 as a potential molecular target and highlight the synergistic efficacy of IONPs and Ara-C in AML treatment.